PREGNANCY CLASS FOR A HEALTHY GENERATION - Pertiwi, Nur Fitri Ayu; Abida, Liza Laela; Nurlaili, Helmi (IFI cabang Kota Bekasi, 2025)
Maternal Mortality Rate (MMR) remains a significant public health challenge in Indonesia. Educational initiatives such as antenatal classes (kelas ibu hamil) serve as strategic promotive and preventive measures to improve maternal knowledge and preparedness for childbirth. This community service activity aimed to enhance pregnant women’s readiness by delivering interactive education covering danger signs during pregnancy, birth planning, family support, and stress management. The program involved 10 pregnant women in Polengan Village, who participated in a pre-test, an educational session, and a post-test. Results showed a significant increase in the average score from 62.5 to 90.0. Notable improvements were observed in knowledge of pregnancy danger signs (from 60% to 90%), planning for delivery and support persons (from 50% to 100%), and awareness of the importance of emotional support and stress management (from 40% to 80%). This program demonstrates that antenatal classes are an effective tool to improve maternal readiness, contribute to reducing MMR, and support the development of a healthier and more empowered future generation. Keywords: antenatal class, maternal mortality, maternal health education, safe pregnancy, community empowerment